Cytotoxicity of titania nanoparticles towards waste water isolate Exiguobacterium acetylicum under UVA, visible light and dark conditions. Issue 3 (September 2015) - Mathur, Ankita; Raghavan, Archanaa; Chaudhury, Pallavi; Johnson, J.B.; Roy, Rajdeep; Kumari, Jyoti; Chaudhuri, Gouri; Chandrasekaran, N.; Suraishkumar, G.K.; Mukherjee, Amitava
Graphical abstract: Highlights: Cytotoxicity of NPs on wastewater bacteria under UVA, visible and dark conditions. Filtered, sterilized wastewater containing Ti ions used as experimental medium. Generation of oxidative stress and damage of TiO2 NPs treated cells. Remarkable surface damage and internalization of TiO2 NPs. Abstract: The aim of the current study was to explore the different modes of the cytotoxicity effects of titania nanoparticles (TiO2 NPs) towards the dominant waste water isolate Exiguobacterium acetylicum at an exposure dose of ≤1 μg/mL in the sterilized and filtered waste water already containing 0.770 ± 0.02 μg/mL dissolved Ti 4+ ions, under different conditions (UVA, Visible Light and Dark). The aggregation behaviour of TiO2 NPs in the experimental matrix was studied for 0.25, 0.5 and 1 μg/mL concentrations at different time intervals (0, 6 and 12 h). The reduction in cell viability under UVA was significantly more than that of other two conditions, i.e., dark and visible light. At 1 μg/mL of titania NPs for an exposure period of 6 h the cell viability with respect to control was found to be as follows: UVA (11.1 ± 0.33%) <visible light (83.8 ± 1.3%) <dark (84 ± 1.3%). The generation of oxidative stress (hydroxyl and superoxide radicals) was more in the bacterial cells exposed to UVA condition as compared to the cells exposed to visible light and dark condition. A significant increase in the membrane permeability was noted under UVA conditions in comparison to that in dark and visible light conditions. The fluorescence microscopy confirmed cell damage due to exposure to the nanoparticles. The scanning electron microscopy (SEM) analysis demonstrated the morphological distortion in the nanoparticle treated bacterial cells. The adsorption and further internalization of nanoparticles were confirmed by transmission electron microscopy (TEM) and elemental analysis.